Effectiveness of technology-integrated arts education in enhancing creativity and SDGs literacy among elementary students - Arina Restian; Anggun Febriyanti (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
This research aims to analyze the effectiveness of implementing Technology-Integrated Arts Education in simultaneously enhancing creativity and Sustainable Development Goals (SDGs) Literacy among elementary school students. The background of this study is the urgent need to prepare the younger generation with 21st-century skills, particularly creativity, as well as global awareness regarding sustainability issues. This study employed a quasi-experimental non-equivalent control group design involving 64 fourth-grade students (n=32 experimental, n=32 control). Data were collected using the Torrance Test of Creative Thinking (TTCT) and the Elementary SDGs Literacy Scale (ESL-S) administered before and after the eight-week intervention. Results from the one-way ANCOVA revealed that the Technology-Integrated Arts Education model was significantly more effective than conventional learning for enhancing creativity (F(1, 61) = 145.32, p < 0.001, η² = 0.48) and SDGs literacy (F(1, 61) = 162.18, p < 0.001, η² = 0.52). Significant improvements were observed across specific domains, particularly SDG 4 (Quality Education), SDG 12 (Responsible Consumption and Production), SDG 13 (Climate Action), and SDG 15 (Life on Land). These findings suggest that integrating digital tools into art activities facilitates creative expression and instills a contextual understanding of sustainability. This study suggests this intervention as a potential strategy for the Primary School Teacher Education (PGSD) curriculum to prepare future educators in integrating technology, arts, and sustainability.